A Research-Based Design for Inservice Training in Marine Science for Primary, Middle School and High School - Spence, Lundie ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This study determined the status of marine education inclusion into K-12 lessons in North Carolina and reflected some inservice parameters. Analysis of a statewide, K-12 survey indicated: (1) 86% of the teachers responding taught some marine concepts in their classes; (2) the criteria for accessing information differed significantly among primary, middle grade, and secondary teachers; and (3) teachers' perceptions on the priority of marine topics and their confidence in teaching those topics were highly correlated. Inservice training opportunities were fewer for primary and middle grade teachers. Inservice programs should be short in length, executed at the school and involve videos to allow teachers to "see" the environment. Primary teachers seem to want materials ready to use with very little involvement on their part. Secondary teachers appear to be more mobile and more able to manipulate materials and curriculum for their own use. (YP)
ERIC Note: Paper presented at the Annual Meeting of the National Association for Research in Science Teaching (62nd, San Francisco, CA, March 30-April 1, 1989).
Policymakers.
Administrators.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Elementary School Science; Elementary Secondary Education; Inservice Teacher Education; Instructional Materials; Marine Education; Science Curriculum; Science Materials; Science Teachers; Secondary School Science; Surveys; Reports, Research; Speeches/Meeting Papers